Peran Kepemimpinan dalam Mengadaptasi Bisnis ke Era Revolusi Industri Digital: Studi Kasus dan Implikasinya - Rohmaniah , Rita; Sri Pudjiarti, Emiliana (Universitas 17 Agustus 1945 Semarang, 2024)
Abstract. Research shows that leadership plays an important role in improving and reforming schools and education systems in the era of the Fourth Industrial Revolution (Mustiningsih, Maisyaroh, and Ulfatin 2019). In the context of the digital industrial revolution, leaders are not only responsible for academic performance and the proper functioning of schools but are also responsible for all activities carried out by schools (Kurniawan et al. 2023). This revolution includes automation and digitalization of all aspects of the industry to create products that meet consumer needs (Lanang Putra et al. 2021). This revolution also presents challenges for tax reform, including integrating various changes caused by digitalization and the Fourth Industrial Revolution (Mayasari and Narsa 2020). In the field of education, leadership abilities in understanding and using digital knowledge are very important to support learning activities in the era of the Fourth Industrial Revolution (Sugiarto and Dewantara 2021). The leadership qualities demonstrated by Christ are very important for pastors in the era of the Fourth Industrial Revolution to be able to lead effectively and overcome challenges (Eppang 2022). The fourth industrial revolution offers opportunities to increase savings and reduce consumption through the development of e-commerce and the digital economy (Suwardana 2018). In addition, this Revolution has also changed job design, job structure, and required skills, thereby increasing the demand for people with different skills (David 2021). Finally, business orientation, digital capabilities, leadership skills, and the environment influence business decisions (Justin and Handoyo 2023).